P02.01 Analysis of Multimodal Intraoperative Monitoring During Intramedullary Spinal Ependymoma Surgery. (6th September 2019) - Park, J; Kim, J; Shin, M; Choi, D
Abstract: BACKGROUND: To evaluate the validity of intraoperative somatosensory-evoked potential (SSEP) and motor-evoked potential (MEP) monitoring according to two different warning criteria for 6 months after intramedullary spinal ependymoma (IMSE) surgery. MATERIAL AND METHODS: To evaluate the validity of intraoperative somatosensory-evoked potential (SSEP) and motor-evoked potential (MEP) monitoring according to two different warning criteria for 6 months after intramedullary spinal ependymoma (IMSE) surgery. RESULTS: The success rates of SSEP and MEP monitoring were 84.9% and 83.7%, respectively. There was one indeterminate case in SSEP and six in MEP. All-or-none criterion in SSEP and MEP monitoring showed higher specificity, PPV, and DOR than 50% decline criterion during 6 months. During the follow up, 37 of 38 extremities (97.4%) and 21 of 29 extremities (72.4%) were observed the improvement of sensory and motor deficit, respectively. Seven indeterminate cases also showed good clinical outcomes. However, most patients remained some degree of neurologic deficit. CONCLUSION: Many false positive and false negative results of SSEP and MEP monitoring occurred immediately postoperative period. All-or-none criterion was more beneficial for IMSE surgery than 50% decline criterion. This trend was maintained until 6 months after surgery.